2018
DOI: 10.1109/tpwrs.2017.2789205
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Frequency Response From Controlled Domestic Heat Pumps

Abstract: The capability of domestic heat pumps to provide dynamic frequency response to an electric power system was investigated. A thermal model was developed to represent a population of domestic heat pumps. A decentralized dynamic control algorithm was developed, enabling the heat pumps to alter their power consumption in response to a system frequency. The control algorithm ensures a dynamic relationship between the temperature of building and grid frequency. The availability of heat pumps to provide low-frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…This implies that heat pumps could smooth heat demand across the day and suggests the potential for flexible operation of many heating systems. Muhssin et al (2018) [70] demonstrated how thermal inertia of buildings equipped with heat pumps can be used to control the electricity consumption for heating and consequently provide dynamic frequency response to the GB power system.…”
Section: Principles For Smart Heat Decarbonisationmentioning
confidence: 99%
“…This implies that heat pumps could smooth heat demand across the day and suggests the potential for flexible operation of many heating systems. Muhssin et al (2018) [70] demonstrated how thermal inertia of buildings equipped with heat pumps can be used to control the electricity consumption for heating and consequently provide dynamic frequency response to the GB power system.…”
Section: Principles For Smart Heat Decarbonisationmentioning
confidence: 99%
“…OSs in [48][49][50][51] optimize PS's power flows using the residential demand-response service. Specifically, the OS in [48] controls the power consumption of domestic heat pumps in response to a PS frequency, and the OS in [49] controls a group of heating, ventilation, and air-conditioning loads. The OS in [51] combines the centralized and decentralized approach.…”
Section: Ps Oss Regulating the Power Consumption During The Optimizatmentioning
confidence: 99%
“…Domestic appliances such as electric water and space heaters, air conditioners, and heat pumps make use of inherent thermal inertia and can be built to aid in the system frequency regulation [4] while minimising the impact on end-users. For example, in the U.K., domestic heat pumps have become common, and it has been estimated that they could provide a frequency regulation capacity of 2 GW by 2030 [5].…”
Section: Introductionmentioning
confidence: 99%
“…This was used to estimate the effect of DLC application to the VSHP on the building indoor air temperature. The work in [5] presented a thermodynamic model of the entire population of localised load controlled heat pumps connected to the U.K. power system, but it only reflected the frequency response based on an on/off control of the heat pump. The works in [9,10] presented a hardware demonstration of VSHP participating in frequency response through a centralised control signal.…”
Section: Introductionmentioning
confidence: 99%